Pendekatan Positive Narrative dalam Penulisan Naskah Animasi “Aku Jaga Tubuhku” Sebagai Media Literasi Perlindungan Diri Anak - Azmi Maharani; Encang Saepudin; Heru Ryanto Budiana (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
The number of cases of sexual violence against children in Indonesia remains alarming, particularly among elementary school-aged children. One factor contributing to children's high vulnerability is a lack of understanding of body boundaries and self-protection. Furthermore, education about the body and self-protection is often considered taboo, resulting in inadequate communication with children. This article discusses the application of a positive narrative approach in writing an educational animation script entitled "Aku Jaga Tubuhku" (I Take Care of My Body) as a self-protection literacy medium for children aged 6–9 years. The research used a descriptive method, outlining the script design process through pre-production, production, and post-production stages. The positive narrative approach was implemented through the development of story, dialogue, characters, and conflict that emphasize child empowerment without creating excessive fear. The results indicate that this approach can help children understand the concepts of body boundaries, safe touch, and unsafe touch in a more concrete and emotionally secure manner. The integration of song elements as memory aids also strengthens children's understanding and retention of the message. Thus, writing an animation script based on a positive narrative can be an effective educational communication strategy for conveying self-protection literacy to elementary school-aged children.